دراسة لنموذج القيمة الاقتصادية المضافة كأداة مكملة لأدوات تقويم أداء الشركات الصناعية والتعديلات المقترحة لاحتسابها: دراسة تطبيقية (Journal of Accounting and Financial Studies ( JAFS ), 2010)
This research aims to analyze and explain the economic advantage to the concepts and measures that are related with added economic value.Added economic value is considered as one of efficient tools which evaluates the performance of corporated  industrial companies. in addition to that the research studied the traditional accounting measure which is used in evaluation of the project and industrial companies.The research tested and analyzed the added economic value measure in some industrial companies and reached to a major recommendation:• We must replace the traditional measure by the new measure that accounts the added value.• We have to train all the workers whom working in the levels of administration to use add value measure.• It is very necessary to connect the moltive system with add value measure in order to increase the bond of workers and securities holders with the administration.